Expression of SOCS1 and CXCL12 Proteins in Primary Breast Cancer Are Associated with Presence of Circulating Tumor Cells in Peripheral Blood - Bozena Smolkova; Michal Mego; Viera Horvathova Kajabova; Zuzana Cierna; Ludovit Danihel; Tatiana Sedlackova; Gabriel Minarik; Iveta Zmetakova; Tomas Krivulcik; Paulina Gronesova; Marian Karaba; Juraj Benca; et al. (Translational Oncology, 2016)
Circulating tumor cells (CTCs) are independent prognostic factors in the primary and metastatic breast cancer patients and play crucial role in hematogenous tumor dissemination. The aim of this study was to correlate the presence of CTCs in peripheral blood with the expression of proteins in tumor tissue that have a putative role in regulation of cell growth and metastatic potential. This prospective study included 203 primary breast cancer patients treated by definitive surgery. CTCs were detected by quantitative real-time PCR for the expression of epithelial (CK19) or epithelial-to-mesenchymal transition–inducing transcription factor genes (TWIST1, SNAIL1, SLUG, and ZEB1). Expression of APC, ADAM23, CXCL12, E-cadherin, RASSF1, SYK, TIMP3, BRMS1, and SOCS1 proteins in primary breast tumor tissue was evaluated by immunohistochemistry. CTCs with epithelial markers were found in 17 (9.2%) patients. Their occurrence was associated with inhibition of SOCS1 expression (odds ratio [OR] = 0.07; 95% confidence interval [CI], 0.03-0.13; P < .001). CTCs with positive epithelial-to-mesenchymal transition markers were detected in 30 (15.8%) patients; however, no association with analyzed protein expressions was found. Overall, CTCs were detected in 44 (22.9%) patients. Presence of any CTC marker was significantly associated with positive CXCL12 expression (OR = 3.08; 95% CI, 1.15-8.26; P = .025) and lack of SOCS1 expression (OR = 0.10; 95% CI, 0.04-0.25; P < .001) in patient’s tumor tissues. As both CXCL12 and SOCS1 proteins are involved in cytokine signaling, our results provide support for the hypothesis that aberrant signaling cross talk between cytokine and chemokine responses could have an important role in hematogenous dissemination of tumor cells in breast cancer.